Cloud Computing and the Common Man. - Viega, John (Computer (00189162), 2009)
The article discusses the advantages as well as the risks of cloud computing. The three major cloud systems categories are software-as-a-service (SaaS), platform-as-a-service (PaaS), and infrastructure-as-a-service (IaaS). The risk factor in the three categories lies in the authentication and encryption methods used, and the plaintext protocols with passwords. The maintenance of data backups is advised when using cloud computing.